Dano eleitoral: an??lise econ??mica da responsabiliza????o por dano moral coletivo do governante cassado - Andrade, Thiago Lemos de (2016)
This work investigates, from an economic perspective, the liability for collective nonpecuniary damages of rulers whose elective mandates are revoked by virtue of committing electoral offense. Underlying the constitutional and legal rules that commands repetition of elections in the event of vacancy in the elected office, there can be seen a trade-off between collective wealth and political representation. Based in these parameters, it is possible to build up a function to assess the deficit of social welfare caused by illegitimately elected candidates taking office and exercising the mandates. This deficit, which corresponds to the economic definition of damages, despite sometimes having a pecuniary component - given the expenses necessary to repeat the elections -, always has a non-pecuniary element, consisting precisely in the partial or total frustration of the political preference for direct democratic representation. As civil liability only fulfills its internalization function in that it promotes perfect compensation, damages payable by the illegitimate officials must encompass a portion to compensate society for that non-pecuniary damages. Moreover, as the collective nonpecuniary damages in discussion, unlike the material damages, has not a fixed amount, but escalates during the time in which the illegitimate officials hold the power - or prevent legitimate ones to hold it -, the compensation also increases due to time. This makes the liability for non-pecuniary damages to have a deterrent effect over purely procrastinatory behavior by defendants in mandate revocation lawsuits. Procrastinatory behavior that, under a regime of civil liability limited to pecuniary damages, is a strongly dominant strategy.